1994
DOI: 10.3181/00379727-207-43801
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Autoantigens of Immunoglobulins and T-Cell Receptors: Their Recognition in Aging, Infection, and Autoimmunity

Abstract: Immunoglobulins and their close relatives, the antigen-specific T-cell receptors, are recognition proteins that express structures which readily serve as self-immunogens. Healthy humans can produce antibodies against variable region-defined recognition structures termed idiotypes, as well as against constant region structures, and the levels of these can increase markedly in autoimmune disease; e.g., rheumatoid factors are autoantibodies directed against a conformational determinant of the gamma heavy chain. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 30 publications
2
23
0
Order By: Relevance
“…Fields et al [49] showed that Vb CDR1 and HV4, as well as CDR2, bound in a cleft between the two domains of the SAgs and that the CDR3 did not have direct contacts. There is thus considerable overlap between the SAg-binding sites of MHCrestricted TCR which supports our hypothesis that the Vb CDR1 is a regulatory idiotope [4] susceptible to modulation by binding of autoantibodies. In the amplification of the SAg response, it is likely that the monoclonal autoantibodies can contribute by binding to CDR1 when SAg contact might be optimal.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Fields et al [49] showed that Vb CDR1 and HV4, as well as CDR2, bound in a cleft between the two domains of the SAgs and that the CDR3 did not have direct contacts. There is thus considerable overlap between the SAg-binding sites of MHCrestricted TCR which supports our hypothesis that the Vb CDR1 is a regulatory idiotope [4] susceptible to modulation by binding of autoantibodies. In the amplification of the SAg response, it is likely that the monoclonal autoantibodies can contribute by binding to CDR1 when SAg contact might be optimal.…”
Section: Discussionsupporting
confidence: 85%
“…The detection of autoantibodies directed against peptide defined epitopes of the T-cell receptor (TCR) b chain in normal sera and various physiological and disease states has been established in our laboratory using synthetic overlapping peptides and subsequent synthetic peptide epitope homologue analysis [1][2][3][4]. Initially, 22 nested synthetic 16-mer peptides were synthesized with five residue overlaps in order to mimic the covalent structure of the TCR b chain for epitope mapping studies of the Bence-Jones protein Mcg (l light chain: see [5]) and the YT35 TCR b gene product (TCR Vb8.1 human: see Refs 1,4 and 6).…”
Section: Introductionmentioning
confidence: 99%
“…A set of overlapping 16-mer peptides that duplicate covalent structure of the VbDbJbCb protein 10,16 predicted from a human TCR-b gene sequence 17 has been produced. TCR Vb CDR1 has a sequence, C K P I S G H N S L F W Y R Q T, that corresponds to the completed CDR1 and N-terminal five residues of Fr2 10,18 of the human Vb8.1 gene product.…”
Section: Peptidesmentioning
confidence: 99%
“…Activated T cells, which exhibit a higher density of many surface membrane antigens than do resting cells and also express neoantigens, were found to be special targets of such autoantibodies [8]. Considerable information also has accrued concerning IgM ALAB target antigens: IL-2 receptor [9]; b 2 -microglobulin [10,11]; HLA class I heavy chains [12]; a DR framework epitope [13]; IgD, which functions as an antigen receptor on B cells [14]; B and T cell membrane glycosphingolipids [15]; CD45 [16][17][18]; and synthetic T cell receptor (TCR) peptides [19]. Almost certainly, there are additional specificities that have not yet been characterized.…”
mentioning
confidence: 99%